2020
DOI: 10.21203/rs.3.rs-25242/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of genomic alterations of perineural invasion in patients with stage II colorectal cancer

Abstract: Background The molecular mechanism of perineural invasion (PNI) in stage Ⅱ colorectal cancer (CRC) remains not to be defined clearly. This study aims to identify the genomic aberrations related to PNI in stage Ⅱ CRC.Methods Using array-based comparative genomic hybridization (array-CGH), primary tumor tissues and paracancerous normal tissues of stage Ⅱ CRC from 5 patients with PNI and 5 patients without PNI were analyzed. We also identified genomic aberrations by using Genomic Workbench and MD-SeeGH. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“… 27 Compared with PNI-positive patients, the expression of FLT1, FBXW7, FGFR1, SLC20A2, and SERPINI1 was significantly up-regulated in PNI-negative group. 28 However, detailed molecular mechanism of TD and PNI still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Compared with PNI-positive patients, the expression of FLT1, FBXW7, FGFR1, SLC20A2, and SERPINI1 was significantly up-regulated in PNI-negative group. 28 However, detailed molecular mechanism of TD and PNI still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MRI‐based radiomics has only been used to investigate LVI in breast and endometrial cancer 33,34 . In previous studies, several researchers have analyzed subjective imaging characteristics determined by radiologists and combined clinical–pathological or gene expression factors to predict LVI/PNI in patients with CRC before surgery 7,35 . However, there had been no reports on lymphovascular invasion of rectal cancer using radiomics until a recent study by Zhang et al 19 .…”
Section: Discussionmentioning
confidence: 99%
“…33,34 In previous studies, several researchers have analyzed subjective imaging characteristics determined by radiologists and combined clinical-pathological or gene expression factors to predict LVI/PNI in patients with CRC before surgery. 7,35 However, there had been no reports on lymphovascular invasion of rectal cancer using radiomics until a recent study by Zhang et al 19 that found a multimodal (MR/CT) radiomics model to have excellent sensitivity (93.8%) but limited specificity (72.7%) for detecting lymphovascular invasion in rectal cancer. Radiomics mainly improves the prediction performance of medical images by improving analysis and using computer algorithms to extract thousands of quantitative features.…”
Section: Discussionmentioning
confidence: 99%